Juridical Study of Forest Area Conversion into Agricultural Land in Tamit Village - Handipan H. Ali; Dolot Alhasni Bakung; Fitran Amrain (Yayasan Cerdas Pedia Indonesia, 2026)
This study analyzed the juridical changes in the function of forest areas into agricultural land in the village of Tamit, Bunobogu District. The research uses empirical legal methods with a socio-legal approach through observation, interviews, and literature studies. The results showed that land use by the community obtained a legal basis after the area of Tamit village was designated as another Use Area (APL) based on SK 6624/MENLHK-PKTL/KUH/PLA.2/10/2021. Legal certainty is strengthened through land certification, especially PTSL programs, which transform factual control into juridical rights. However, Forestry supervision is still needed so that land use does not exceed APL limits. The synchronization of forest, land, and community participation laws is the key to legal protection.